Responses of lactating Holstein cows to increasing amounts of wet corn gluten feed - John F. Smith; K. Grigsby; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2006)
Forty lactating Holstein cows were allocated into groups of 5 cows each and assigned to 8 pens containing 10 freestalls each. Each group contained 3 heifers and 2 multiparous cows. Groups were balanced by milk production and days in milk. Diets were formulated to contain none (control), 12, 24, or 36% wet corn gluten feed (WCGF) on a dry matter (DM) basis. Increasing amounts of WCGF and heat-treated expeller soybean meal replaced a portion of the corn silage, alfalfa hay, corn grain, soybean meal, and soybean hulls of the control diet to maintain similar concentrations of crude protein (CP), ruminally undegraded crude protein (RUP), and neutral detergent fiber (NDF). A Latin Square design with 4-week periods was used. Periods were 4 weeks in duration, with 2 weeks of adjustment followed by 2 weeks of data collection. Milk weights were recorded at each milking, and weekly milk samples (a.m. and p.m.) were collected for milk component analysis. Milk and feed data were averaged by pen and week before analysis. Milk production, energy-corrected milk production, and efficiency of energy-corrected milk production increased with increasing amounts of WCGF. Dry matter intake was unaffected by diet. These data indicate that WCGF can be utilized effectively at 36% of the ration DM if concentrations of RUP, CP, and NDF are maintained in the diet.; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Dairy Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; By-products; Nutrition; Wet corn milling